The Influence of the Viscoelasticity on the Axisymmetric Wave Attenuation in a bi-Material Solid Cylinder - Kocal, T.; Akbarov, S. D. (POLISH ACAD SCIENCES INST PHYSICS, 2018)
This paper studies the attenuation of the axisymmetric longitudinal waves propagating in a bi-material compound solid cylinder made of viscoelastic materials, the constitutive relations of which are described by utilizing the fractional exponential operators of Rabotnov. Rheological parameters are introduced and through these parameters the influence of the material viscosity on the attenuation coefficient of the propagating waves is investigated. Numerical results of the attenuation dispersion and the corresponding dispersion curves are presented and discussed. In particular, it is established that the dependence between the coefficient of attenuation and a certain rheological parameter can have a non monotonic character.
Keywords: LAYERED HOLLOW CYLINDER; LONGITUDINAL-WAVES; DISPERSION; Physics